G87(P) Assessing the unmet health needs of children seen after suspected child sexual assault. (May 2019) - Coleman, C; Finnis, M
Abstract : Introduction: Children who present for medical assessment after suspected sexual abuse (CSA) often have a high level of health needs that may not have been previously identified. Children who may have suffered sexual abuse should have a holistic assessment, going beyond forensic examination, covering their general physical, emotional and mental health as well as considering factors about education and wider family issues. Aim: The aim of this study was to identify how often the CSA medical leads to unmet health needs, not directly related to the presenting CSA concern, being identified and addressed. Method: In our region, children under 13 years of age are seen in the Community paediatric service, with support from local SARC (sexual assault referral centre) in acute cases. All new cases seen in the Community paediatric department from January to October 2018 were identified and notes were reviewed. All data was anonymised. Information was collected about general health needs identified during CSA examination, and any subsequent referrals and follow up arranged. Results: 25 cases were seen in the department for CSA examination between January and October 2018. 48% had untreated health needs identified and of these, 75% were not directly related to the presenting concern. Unmet health needs identified included constipation, untreated eczema, head lice and dental caries. Signs and symptoms of neglect were identified in several children. 20% of the cases seen were referred to another medical or surgical service, with 60% requiring follow up within community paediatrics. Conclusions: In our experience the CSA medical assessment often identifies significant unmet health needs. The paediatric assessment in CSA is more than a forensic assessment and plays an important role in supporting vulnerable children. Follow-up within community paediatrics and close working between paediatric teams enhances continuity of care and can be important in ensuring that health needs are addressed. An understanding of the holistic nature of paediatric CSA medicals may be helpful to other professionals when planning care of children after suspected sexual abuse.